PENGARUH ENVIRONMENTAL PERFORMANCE, MATERIAL FLOW COST ACCOUNTING, DAN GREEN ACCOUNTING TERHADAP SDGs (Studi Berbasis Data pada Perusahaan Manufaktur Subsektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2022–2024) - Rosmida; Mubarak, Husni; Suhadi, Agus; Santia , Eni (Jurnal Riset Terapan Akuntansi, 2025)
The focus of this study is to examine “the influence of Environmental Performance, Material Flow Cost Accounting (MFCA), and Green Accounting on Sustainable Development Goals (SDGs) in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024.” The data used was sourced from annual reports and sustainability reports, which were collected through documentation and literature review methods. The research sample was determined using the purposive sampling technique, including 20 companies over three years of observation, resulting in 60 observations. After cleaning the outlier data, the number of samples suitable for analysis was reduced to 47. Multiple linear regression analysis was performed using SPSS version 25 software. The study found that, partially, Environmental Performance and Green Accounting had no impact on SDGs, while MFCA had a positive and significant impact. Simultaneously, these three independent variables have an impact on SDGs. This study states that the application of MFCA plays a real role in supporting the achievement of SDGs, while Environmental Performance and Green Accounting are still not fully integrated into corporate sustainability strategies. Keywords: environmental performance, material flow cost accounting, green accounting, sustainable development goals.